Health Literacy and its Related Factors in Patients with a History of Open Heart Surgery - Salman Khazaei; Hadi Soori; Mohammad Hossein Bakhshaei; Seyed Ahmad Raza Salim Bahrami (پزشکی بالینی ابن سینا, 2022)
Background and Objective:Cardiovascular diseases are a common disorder, and some patients undergo open heart surgery due to the severity of the disease and lack of response to drug treatment. Following surgery, these patients require adequate health literacy to make informed decisions and perform self-care behaviors. This study aimed to determine the health literacy and its related factors in patients with a history of open heart surgery in Farshchian Cardiology Hospital in Hamadan, Iran, during 2020. Materials and Methods:This cross-sectional study selected 278 patients by available sampling method from those who were referred to a Cardiology Hospital in Hamadan and underwent open heart surgery. The patients were evaluated in terms of health literacy using a standard questionnaire, which assessed patients' health literacy in 5 areas of access, reading skills, comprehension, evaluation/decision-making, and the use of health information. Data were analyzed in SPSS software at a 95% confidence level. Results:The mean age of the patients was 48.62±14.04 years, and the majority of them were female (52.90%). Furthermore, 64.39% of the participants had poor or moderate health literacy. The Internet (49.60%) and health workers (32.40%) were the most important sources of receiving health information. Health literacy showed a significant relationship with patients' gender and education level (P<0.05). Conclusion:Patients with a history of open heart surgery do not have good health literacy, and it is necessary to plan for the promotion of health literacy in them. In this regard, health workers have an important role in increasing the level of health literacy; moreover, they should spend more time educating patients appropriate to their age and education level.